MODELS INVOLVEMENT OF PARENTS IN GROWING RELIGIOUS CHARACTERS IN EARLY CHILDHOOD - Sofyan, Agus; Suharti, Lety; Hardiyanto, Edy; Mulyono, Dinno (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2020)
This research departs from the field findings that the role of parents in inculcating religious character still lacks the proper portion, thus impacting children's understanding of religious values universally. With this model implemented in some PAUD units it is hoped that it will become a model that is ready to be used in other locations in order to develop religious values for early childhood. This research approach uses quantitative research methods with an instrument in the form of a questionnaire. The results of this study indicate that there are some changes in the understanding and behavior of parents in instilling religious character in early childhood. The main conclusion of this study is the model of involving parents in developing the religious character of early childhood provides a change in the attitude and understanding of parents in carrying out religious values in the family.